KAJIAN TEKNIS DAN EKONOMIS PENGGUNAAN LPG DAN BENSIN PREMIUM SEBAGAI BAHAN BAKAR MOTOR BENSIN 4 TAK PADA KAPAL NELAYAN TRADISIONAL - Reza Shah Alam; Ari Wibawa Budi Santosa; Untung Budiarto (Jurnal Teknik Perkapalan, 2013)
The uses of fuel gas as an alternative energy resources is the one of potential option to decrease the high number of consumption of oil fuel in human society. LPG can be a potential fuel resources to a fisherman because it is easy to find than the others gasses. This research is the technical and economical research of LPG and premium gasoline as a fuel of gasoline engine 4 stroke on a traditional fisherman ship. This research is through 2 step of primary data taken, that is laboratorium experiment that is held on engine lab of BBPPI semarang and field experiment that is held on Tanjung Mas the harbor of Semarang. The results of this research is on Honda GX 200 6,5 hp gasoline engine the using of LPG fuel at low rpm (1600 – 1800 rpm) it has a higher power, but at a higher rpm the power of premium gasoline fuel is has a higher power. The economical research is the uses of LPG fuel is more economic than premium gasoline on a operational fuel cost, but LPG uses is not economic in an set up investation.